Tasybih sebagai Retorika Representasi Imajinatif pada Diwan Qaalat Lii As-Samra karya Nizar Qabbani: Kajian Ilmu Bayan - Al-Fadhil, Arinal Faiz; Akmaliyah, Akmaliyah; Pauji, Resa Restu (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2026)
Tasybih, as one of the central rhetorical devices in Arabic balaghah, plays an important role in creating linguistic beauty and clarifying meaning in Arabic literary works, especially poetry. This diwan was selected as the object of study because it is one of Qabbani’s early poetry collections that contains many figurative expressions, yet it has not been widely examined from the perspective of Tasybih through an ʿIlm al-Bayan approach. This study aims to analyze the types and functions of Tasybih in Diwan Qaalat Lii as-Samra’ by Nizar Qabbani based on the framework of ʿIlm al-Bayan. This research employs a descriptive qualitative method with a rhetorical (balaghah) approach. The data consist of poetic verses containing Tasybih found in the diwan. Data were collected through observation and note-taking techniques, while analysis was conducted using immediate constituent analysis, translational techniques, and deletion techniques to identify the structure, types, and functions of Tasybih more precisely. The findings show that several types appear, including Tasybih mursal, mu’akkad, mufashshal, baligh, and ḍhimni. Their functions include explaining possibility, describing the state of the Musyabbah, strengthening or weakening its image, and clarifying poetic imagery in the text. This study contributes to Ilm al-Bayan scholarship and Arabic poetry.Keywords - Balaghah, Ilm al-Bayan, Nizar Qabbani, Qaalat Lii as-Samra), Tasybih.